Mutated lamin A modulates stiffness in muscle cells - Chatzifrangkeskou, Maria; Kah, Delf-Thorge Eric; Lange, Janina; Goldmann, Wolfgang; Muchir, Antoine (Biochemical and Biophysical Research Communications, 2020)
The cytoskeleton is a complex network interlinking filaments that extend throughout the cytoplasm from the nucleus to the plasma membrane. Three major types of filaments are found in the cytoskeleton: actin filaments, microtubules, and intermediate filaments. They play a key role in the ability of cells to both resist mechanical stress and generate force. However, the precise involvement of intermediate filament proteins in these processes remains unclear. Here, we focused on nuclear A-type lamins, which are connected to the cytoskeleton via the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex. Using micro-constriction rheology, we investigated the impact of A-type lamins (p.H222P) mutation on the mechanical properties of muscle cells. We demonstrate that the expression of point mutation of lamin A in muscle cells increases cellular stiffness compared with cells expressing wild type lamin A and that the chemical agent selumetinib, an inhibitor of the ERK1/2 signaling, reversed the mechanical alterations in mutated cells. These results highlight the interplay between A-type lamins and mechano-signaling, which are supported by cell biology measurements.
CRIS-Team Scopus Importer:2020-06-19
Keywords: A-type lamin (LMNA); Cell mechanical properties; Cell nucleus; Chemical substance selumetinib; ERK1/2 signaling; Micro-constriction rheology